Effects of acute ethanol and/or diazepam exposure on immediate and delayed hippocampal metabolite levels in rats anesthetized with isoflurane. (17th February 2022) - Carton, Louise; Auger, Florent; Laloux, Charlotte; Durieux, Nicolas; Kyheng, Maéva; Potey, Camille; Bergeron, Sandrine; Rolland, Benjamin; Deguil, Julie; Bordet, Régis
Abstract: Alcohol and benzodiazepines are psychoactive substances frequently associated in voluntary drug intoxications that share common mechanisms of action, including facilitation of GABAergic transmission. This study aimed to assess the separate and combined effects of ethanol and diazepam acute exposure on hippocampal metabolite levels, as well as on delayed cognitive performance, in rats anesthetized with isoflurane. Adult male Wistar rats received one intraperitoneal injection containing either saline solution ("CTL" group, N = 15), a 5‐mg/kg dose of diazepam ("DIA" group, N = 16), a 2‐g/kg dose of ethanol ("EtOH" group, N = 18), or a 5‐mg/kg dose of diazepam + a 2‐g/kg dose of ethanol ("DIA + EtOH" group, N = 24). The levels of brain metabolites in the hippocampal region were assessed using in vivo magnetic resonance spectroscopy (MRS) before and after injection. Behavioral testing, including working memory and visual recognition memory assessment, was performed at week 3, while a new MRS acquisition was conducted 4 weeks after the injection. In the hour following acute exposure, a decrease in glutamate levels was found in the DIA + EtOH group only. Four weeks after injection, a decrease in GABA and glutamate levels and an increase in NAA levels were found in the EtOH group only. No significant between‐group differences were found in the behavioral assessment. While the initial decrease in glutamate levels in the DIA + EtOH group suggests an early potentiation effect between ethanol and diazepam, the long‐term modifications found only in the EtOH group suggest a possible downregulation of ethanol's effect by diazepam at 4 weeks.